Obstructive sleep apnea is associated with depressive symptoms in pregnancy. Issue 5 (29th November 2019) - Redhead, Karen; Walsh, Jennifer; Galbally, Megan; Newnham, John P; Watson, Stuart J; Eastwood, Peter
Abstract: Study Objectives: In pregnancy, the prevalence of both obstructive sleep apnea (OSA) and depression increases. Research reveals an association in the general population with up to 45% of patients diagnosed with OSA having depressive symptoms. Therefore, this study aimed to investigate the relationship between OSA and depression in pregnant women. Methods: One hundred and eighty-nine women ≥26 weeks pregnant were recruited from a tertiary perinatal hospital. This cross-sectional study measured OSA (Apnea Hypopnea Index, AHI, using an ApneaLink device) and symptoms of depression (Edinburgh Postnatal Depression Scale, EPDS). Data were collected from medical records including participant age, ethnicity, parity, BMI, smoking status, history of depression, and use of antidepressants. Results: Of the consenting women, data from 124 were suitable for analysis. Twenty women (16.1%) had OSA (AHI ≥ 5 events/h) and 11 (8.8%) had depressive symptoms (EPDS > 12). Women with OSA were more likely to have depressive symptoms after adjusting for covariates, odds ratio = 8.36, 95% CI [1.57, 44.46]. OSA was also related to higher EPDS scores and these were greater in women with a history of depression. Conclusions: During late pregnancy women with OSA had eight times the odds of having depressive symptoms. Furthermore, an interaction was found between OSA and history of depression. Specifically, in women with no history of depression, OSA increases depressive symptoms. In women with a history of depression, OSA has an even stronger effect on depressive symptomology. This suggests screening for OSA in pregnancy may identify women prone to future depressive episodes and allow for targeted interventions.